2018
DOI: 10.1177/155892501801300209
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of Break Draft, Pin Spacer and Rubber Cots Hardness to Enhance the Quality of Ring Spun Yarn Using Factorial Design

Abstract: The aim of the present work is to optimize the drafting parameters for ring spinning by using full factorial (2 3) experimental design. Three drafting parameters of ring spinning each at two levels were chosen for this study. These technological parameters were break draft, size of pin spacer and hardness of rubber cots. It was found from statistical analysis that pin spacer size has a significant effect on yarn unevenness (U %), imperfection index (IPI), hairiness (H) and yarn strength (CLSP) compared to the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…The draft quality as well as the ultimate yarn quality is the combined effect of the interaction of these influencing variables with the fibrous material. The optimization of draft zone settings using different modeling and optimization techniques has been the topic of research in last few decades [1][2][3][4][5][6][7][8]. Similar researches had been carried out for the rotor spun yarns [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…The draft quality as well as the ultimate yarn quality is the combined effect of the interaction of these influencing variables with the fibrous material. The optimization of draft zone settings using different modeling and optimization techniques has been the topic of research in last few decades [1][2][3][4][5][6][7][8]. Similar researches had been carried out for the rotor spun yarns [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…Although the advanced spinning technologies have solved the problem of production and automation to a great extent, the conventional ring spinning dominates the staple yarn spinning techniques due to its high quality, high strength, and flexibility compared to innovative spinning processes [1]- [3]. As ring frame cost comprises a major portion of total cost, the productivity at ring frame has assumed considerable importance and every effort to maximize production at this stage is worth exploring.…”
Section: Introductionmentioning
confidence: 99%
“…The parameters were selected as break draft, pin spacer size and rubber cots' hardness. Statistical analyses indicated that pin spacer size has significant effect on yarn unevenness (U%), imperfection index (IPI), hairiness (H) and yarn strength compared to other two chosen factors [8]. Yılmaz and Uysal improved various nozzles having different injector angles, main hole diameters, injector diameters, number of injectors, nozzle shapes and injector positions in order to reduce hairiness of siro-jet yarns m [9].…”
Section: Introductionmentioning
confidence: 99%